The Secreted Virulence Factor NADase of Group A Streptococcus Inhibits P2X7 Receptor-Mediated Release of IL-1β - Westerlund, Elsa; Valfridsson, Christine; Yi, Daisy X.; Persson, Jenny J. (Frontiers in Immunology, 2019)
The common human pathogen Group A Streptococcus (GAS) causes superficial as well as invasive, life-threatening diseases. An increase in the occurrence of invasive GAS infection by strains of the M1 and M89 serotypes has been correlated with increased expression of the genetically and functionally linked virulence factors streptolysin O and β-NAD+-glycohydrolase (NADase). NADase affects host cells differently depending on its location: its SLO-dependent translocation into the cytosol can lead to cell death through β-NAD+ depletion, while extracellularly located NADase inhibits IL-1β release downstream of Nlrp3 inflammasome activation. In this study, we use a macrophage infection model to investigate the NADase-dependent inhibition of IL-1β release. We show that a NADase-deficient GAS strain activates the P2X7 receptor leading to increased IL-1β release, while bacteria expressing a functional NADase evade P2X7 activation. Further, our data indicate that in the absence of NADase, the leaderless cytokine IL-1β is simultaneously released through both P2X7-dependent and -independent mechanisms. This study contributes to a deeper understanding of the NADase-dependent immune evasion mechanism employed by GAS, while simultaneously shedding light on non-classical protein release of the important inflammatory cytokine IL-1β during bacterial infection.